2014
DOI: 10.1242/dmm.016980
|View full text |Cite
|
Sign up to set email alerts
|

The utility of Apc-mutant rats in modeling human colon cancer

Abstract: Prior to the advent of genetic engineering in the mouse, the rat was the model of choice for investigating the etiology of cancer. Now, recent advances in the manipulation of the rat genome, combined with a growing recognition of the physiological differences between mice and rats, have reignited interest in the rat as a model of human cancer. Two recently developed rat models, the polyposis in the rat colon (Pirc) and Kyoto Apc Delta (KAD) strains, each carry mutations in the intestinal-cancer-associated aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 98 publications
1
69
0
1
Order By: Relevance
“…For example, Chuang et al (19) found reduced neutrophil counts in castrated males that could be restored to normal levels through androgen supplementation, implicating the innate immune system. Our evidence that testosterone acts indirectly to promote colonic adenomagenesis opens the possibility of testing these indirect mechanisms, using the power of the molecular genetics of the mouse and rat to ablate the Ar gene in somatic lineages that are candidates for the site of testosterone action (20).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Chuang et al (19) found reduced neutrophil counts in castrated males that could be restored to normal levels through androgen supplementation, implicating the innate immune system. Our evidence that testosterone acts indirectly to promote colonic adenomagenesis opens the possibility of testing these indirect mechanisms, using the power of the molecular genetics of the mouse and rat to ablate the Ar gene in somatic lineages that are candidates for the site of testosterone action (20).…”
Section: Discussionmentioning
confidence: 99%
“…The team report that the mutant shows a distinctive tumour spectrum, the primary tumour types being osteosarcomas and meningeal sarcomas, similar to the early bone and central nervous system (CNS) sarcomas found in humans with Tp53 mutations, but not commonly found in mouse Tp53 mutants. Such commonality with human cancer phenotypes has previously been seen in the Apc mutant Pirc rat, with intestinal tumour distribution more typical of human intestinal tumours than Apc mutant mice (Irving et al, 2014), and in the hormonal responsiveness of rat breast cancer models (Samuelson et al, 2007). This study gives further credence to the translational validity of rat models of human cancer and fills an important gap by providing a new animal model for the study of paediatric osteosarcomas.…”
Section: Original Research Contributions: the Uniqueness Of The Rat Mmentioning
confidence: 59%
“…Drake recognized the vast treasure of stories that Crow had developed, once saying "Someone should attach a recording device around Jim's neck to capture his stories!" A generation younger, I, in contrast, had extensive research experience in molecular biology and development, as heavily influenced by genetics, carrying out research on controlled replication in organisms ranging from bacteriophage to protists to mammals (Furth et al 1979;Moser et al 1990;Burland et al 1993;Dove et al 1998;Irving et al 2014). My extensive contacts in genetics reflect that range of interests.…”
mentioning
confidence: 99%